Versos sencillos Simple verses - Martí, José, 1853-1895 (Recovering the U.S. Hispanic Literary Heritage Project publication., 1997)
A collection of poems that constitutes a spiritual autobiography of José Martí, the renowned Cuban poet, philosopher, and patriot.